Predictive value of risk score using Kyoto classification of gastritis a few years prior to diagnosis of early gastric cancer. Issue 2 (23rd December 2020) - Fujimoto, Yo; Katayama, Yasumi; Gyotoku, Yoshinori; Oura, Ryosuke; Kobori, Ikuhiro; Kitagawa, Tomoyuki; Tamano, Masaya
Abstract: Background and Aim: Based on past diagnostic classifications of gastritis, the Kyoto classification of gastritis adopts simpler, more objective gastritis findings according to Helicobacter pylori infection status and evaluates the risk of gastric cancer. To clarify whether this score can predict future gastric cancer, we retrospectively examined risk scores obtained using the Kyoto classification of gastritis a few years prior to the diagnosis of early gastric cancer. Methods: We reviewed data from 50 individuals who had undergone upper gastrointestinal endoscopy 2–3 years prior to the diagnosis of early gastric cancer in our hospital. Two expert endoscopists evaluated and compared risk scores obtained using the Kyoto classification of gastritis between cancer and control groups. Results: With regard to the risk score obtained using the Kyoto classification of gastritis in all cases, atrophy, intestinal metaplasia, diffuse redness, and total score were significantly higher among gastric cancer cases. Among H. pylori ‐eradicated cases, atrophy score was higher in the gastric cancer group. Among patients for whom H. pylori had been eradicated for >3 years at first endoscopy, atrophy score was still higher in the gastric cancer group. Conclusion: This retrospective study suggested that the risk score obtained using the Kyoto classification of gastritis was useful for predicting the onset of gastric cancer. In particular, patients with a high atrophy score even after H. pylori eradication may be at high risk of developing gastric cancer. Abstract : This retrospective study suggested that the risk score obtained using the Kyoto classification of gastritis was useful for predicting the onset of gastric cancer. In particular, patients with a high atrophy score even after H. pylori eradication may be at high risk of developing gastric cancer.